Evaluation of a novel method for the identification of coevolving protein residues - Pritchard, Leighton; Bladon, Peter; Mitchell, Jane M. O.; Dufton, Mark J. (Protein engineering, 2001)
A novel method for the identification of correlated pairs in aligned homologous protein sequences is presented and evaluated against a model of simulated protein evolution incorporating covariation. Our method is shown to be capable of identifying all coevolutionary pairs of sites, with minimal interference by background correlations, in aligned sequence sets containing approximately 60 sequences with a tree depth of at least 30 accepted point mutations. This result is expected even in the presence of a large degree of neutral and non-correlated evolution. It is postulated that, since naturally occurring protein families may be subject to stronger selection pressures and a lesser degree of neutral evolution, this method of covariation analysis may be generally more robust than the model would indicate.